On the Issue of Verification of the Concept of “Path Dependence” for the Former Soviet Union in the Light of Thirty Years of Intuitive Practices - N. M. Mezhevich (Управленческое консультирование)
Radical reforms cannot be an independent goal of economic development. Since 1990–1991, various management and economic practices have been oriented to various degrees to overcome the “path dependence”. However, it was not possible to get out of the effect of dependence on the previous path more than one country of the Former Soviet Union. D. North’s theory of variable reform processes proved to be ideal for explaining key problems of institutional development of the Former Soviet Union.